2019
DOI: 10.1044/2019_jslhr-h-18-0514
|View full text |Cite
|
Sign up to set email alerts
|

Test–Retest Reproducibility of Response Duration in Tinnitus Patients With Positive Residual Inhibition

Abstract: Purpose Functional imaging is often used to try to elucidate the pathophysiological mechanism of tinnitus. Residual inhibition, the temporary suppression of tinnitus after application of a masking noise, could be an interesting technique to modulate tinnitus perception in functional imaging paradigms. The purposes of this study were to primarily assess reproducibility of the (partial) positive residual inhibition response duration in patients with tinnitus and to explore its utility in experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 68 publications
2
3
0
Order By: Relevance
“…The prevalence of RI observed in our study, i.e. 58 of 74 subjects (78%) with some degree of residual inhibition and 48 subjects (65%) with substantial tinnitus suppression, is comparable to previous studies reporting a prevalence between 61.5% and 88.0% (Deklerck et al, 2019;Vernon and Meikle, 2003;Henry et al, 2000;Roberts et al, 2008). The mean maximum RI time of 93.3 seconds is comparable to the findings of Vernon and Meikle (2003).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The prevalence of RI observed in our study, i.e. 58 of 74 subjects (78%) with some degree of residual inhibition and 48 subjects (65%) with substantial tinnitus suppression, is comparable to previous studies reporting a prevalence between 61.5% and 88.0% (Deklerck et al, 2019;Vernon and Meikle, 2003;Henry et al, 2000;Roberts et al, 2008). The mean maximum RI time of 93.3 seconds is comparable to the findings of Vernon and Meikle (2003).…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies demonstrated that RI can be consistently reproducible between sessions indicating that there is no long-term adaptation affecting test-retest assessment (Roberts et al, 2008;Deklerck et al, 2019). However, the effect of consecutive repeated stimulation on shortterm adaptation and the robustness of RI has not yet been comprehensively studied in human subjects.…”
Section: Short-term Repeatability Of Residual Inhibitionmentioning
confidence: 99%
“…This finding validates that RI can be used to induce repeated states with or without tinnitus in the same subject, which is important in the context of within-subject comparison studies (e.g., Hu et al., 2019). The prevalence of RI observed in our study, that is, 58 of 74 subjects (78%) with some degree of residual inhibition and 48 subjects (65%) with substantial tinnitus suppression, is comparable to previous studies reporting a prevalence between 61.5% and 88.0% (Deklerck et al., 2019; Henry & Meikle, 2000; Roberts et al., 2008; Vernon & Meikle, 2003). The mean maximum RI time of 93.3 seconds is comparable to the findings of Vernon and Meikle (2003).…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies demonstrated that RI can be consistently reproducible between sessions indicating that there is no long-term adaptation affecting test-retest assessment (Deklerck et al, 2019;Roberts et al, 2008). However, the effect of consecutive repeated stimulation on shortterm adaptation and the robustness of RI has not yet been comprehensively studied in human subjects.…”
Section: Short-term Repeatability Of Residual Inhibitionmentioning
confidence: 99%
“…In contrast, the presentation of masking noise causes RI after the end of noise presentation. As RI is a technique to temporarily modulate the tinnitus percept, it is a potential target for experimental studies on tinnitus mechanisms (Deklerck et al, 2019).…”
Section: Residual Inhibitionmentioning
confidence: 99%